Labour Unions, business co-ordination and economic adjustment in Western Europe, 1980-90 - Bob Hancké (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
This paper discusses the development of labour relations during the 1980s in Western Europe. It argues that a proper understanding of the different trajectories indifferent countries cannot be understood by taking into account either state policies or employers preferences alone. Through their local sections, labour unions are ableto impose costs on employers when these want to reorganise firms in order to adapt to changing markets exigencies. Adjustment therefore is conditioned by the organisation of employers in the economy, and of unions in the firm. The paper combines these two dimensions, and discusses their impact upon patterns of adjustment in labour relations during the 1980s in Germany, Sweden, Belgium, theUK, France and the Netherlands – – In dem Papier wird die Entwicklung der Arbeitsbeziehungen in Europa während der achtziger Jahren analysiert. Dabei wird davon ausgegangen, daß ein angemessenes Verständnis der unterschiedlichen Anpassungspfade in den jeweiligen Ländern unmöglich ist, wenn nur auf die staatliche oder die Interessenspolitik der Arbeitgeber Bezug genommen wird. Durch ihre betrieblichen Organisationseinheiten können die Gewerkschaften den Arbeitgebern Kosten aufzwingen, wenn diese ihr Unternehmen reorganisieren wollen, um sich veränderten Marktbedingungen anzupassen. Deshalb wird die Anpassung von dem Organisationsgrad der Arbeitgeber und der Gewerk-schaften in den Unternehmen geprägt. In dem Papier werden diese beiden Dimensionen zusammengefaßt und ihr Einfluß auf Veränderungsmuster in denindustriellen Beziehungen während der achtziger Jahre in Deutschland, Schweden,Belgien, Großbritannien, Frankreich und den Niederlanden diskutiert
Keywords: 330; Arbeitsbeziehungen; Wirtschaftliche Anpassung; Reorganisation; Europa